Hoax Dalam Perspektif Islam - Takdir Alisyahbana (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
Hoax becomes very popular when information technology makes it easy for all social media circles through internet devices either via compiuter or Android mobile. The use of social media for hoax news, can have a negative impact on the morality of the nation's children. The teachings of Islam strongly prohibit humans from spreading false news either through oral or written. Therefore to combat Islamic hoaxes provide accurate solutions, in the form of communication principles.